he Shanghai Cooperation Organization and its role in the contemporary system of international relations (On the 20th anniversary of the SCO) - D. V. Malyshev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2022)
This year marks the 20th anniversary of the Shanghai Cooperation Organization (SCO). This is a good opportunity to assess its performance over the past two decades, to draw some conclusions, and to discuss possible future developments of the SCO. The author examines milestones in the formation of the SCO, its institutional structure, as well as its key activities which encompass four focal areas: politics, security, economy, and humanitarian cooperation. The paper focuses on the decisions of the 21st SCO Summit in Dushanbe, especially those aimed at strengthening cooperation in combating the eﬀ ects of the SARS-CoV-2 pandemic and addressing security challenges, arising from the latest developments in Afghanistan. The latter particularly imply an increasing threat of terrorism, extremism, and drug traﬃ  cking from Afghanistan to neighboring countries in Central Asia. The author emphasizes the crucial role of the SCO Regional Antiterrorist Structure (RATS) in countering these threats. Finally, the paper addresses both the circumstances and possible implications of Iran’s ascension to a full SCO member, which was approved during the summit in Dushanbe. The author concludes that over the past two decades the SCO has successfully transitioned from an important, yet regional in scope and framework, organization to an inﬂ uential global actor, which plays a major role in the maintenance of peace and security in Central Asia and could serve as a model for the establishment of a new non-confrontational approach to the interstate relations.